Molecular Detection and Characterization of Goat Isolate of Taenia hydatigena in Turkey - Armagan Erdem Utuk; Fatma Cigdem Piskin (The Scientific World Journal)
The aim of this study was to provide molecular detection and characterization of the goat isolate of Taenia hydatigena from Ankara province of Turkey. For this purpose, PCR amplification of small subunit ribosomal RNA (rrnS) and partial sequencing of mitochondrial cytochrome c oxidase subunit 1 (mt-CO1) genes were performed in a one-month-old dead goat. According to rrnS-PCR results, parasites were identified as Taenia spp., and partial sequence of mt-CO1 gene was corresponding to T. hydatigena. At the end of the study, we concluded that molecular tools can be used to define species of parasites in cases where the key morphologic features cannot be detected. Nucleotide sequence data of Turkish goat isolate of T. hydatigena was submitted to GenBank for other researchers interested in this subject. By this study, molecular detection and characterization of T. hydatigena was done for the first time in Turkey.